Pengaruh Penyerapan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Di Kota Serang Tahun 2018 – 2021 - Irawan, Patriotika Zahrah; Samosir, Dina Uli Doresta; Sitorus, Alpen Mario Albertus; Ikhsan, Ikrar Ilhamy; Dermawan, Deris (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
The purpose of this study is to analyze the effect of employment on economic growth in Serang City in 2018 – 2021. The variables analyzed are the independent variable, namely employment and the dependent variable, namely economic growth. The analytical method used is a quantitative method using documentary data sourced from the Central Bureau of Statistics (BPS) and using the IBM SPSS tool. After being analyzed, the results of this study show that economic growth has no significant impact on employment. So it cannot be ascertained whether the rate of economic growth in Serang City between 2018 - 2021 will increase or decrease if there is an increase or decrease in employment.